Sovereign Risk Premiums in the European Government Bond Market - Kerstin Bernoth; Jürgen von Hagen; Ludger Schuknecht (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
This paper provides a study of bond yield differentials among EU government bonds issued between 1993 and 2005 on the basis of a unique dataset of issue spreads in the US and DM (Euro) bond market. Interest differentials between bonds issued by EU countries and Germany or the USA contain risk premiums which increase with fiscal imbalances and depend negatively on the issuer's relative bond market size. The start of the European Monetary Union has shifted market attention to debt service payments as the key measure of indebtedness and eliminated liquidity premiums in the euro area.
urn:nbn:de:bvb:19-epub-13400-1
Keywords: G12; E43; E62; H63; 330; asset pricing; determination of interest rates; fiscal policy; government debt